Bridging Ecological Rationality, Embodied Emotion, and Neuroeconomics: Insights From the Somatic Marker Hypothesis - Xu, Fuming; Xiang, Peng; Huang, Long (Frontiers in Psychology, 2020)
Somatic Marker Hypothesis (SMH) has been utilized to demonstrate the role of emotion and somatic state in decision-making under uncertainty over the past two decades. hypothesis. Despite some debate, the SMH has provided not only a neurobiological framework for understanding emotion and decision-making, but also good empirical support for ecological rationality and embodied emotion. Unlike the traditional maximizing rationality and bounded satisficing rationality, the ecological rationality stresses that emotions should be brought to the decision-making process. The embodied emotion furthermore emphasizes that emotions is embodied in the body and the brain. On the other hand, behavioral decision-making has spawned many new interdisciplines, including neuroeconomics. In this case, the SMH could act as a bridge to translate the ecological rationality and the embodied emotion into emerging neuroeconomics. Thus, this mini review article aims to propose an integrated framework for introducing ecological rationality and embodied emotion into the field of neuroeconomics by virtue of insights from the SMH.